An Efficient Synthesis of bi‐Aryl Pyrimidine Heterocycles: Potential New Drug Candidates to Treat Alzheimer's Disease. Issue 3 (21st February 2017) - Rehman, Tanzeel Ur; Khan, Islam Ullah; Ashraf, Muhammad; Tarazi, Hamadeh; Riaz, Sadaf; Yar, Muhammad
Abstract : A series of 13 novel pyrimidine‐based sulfonamides6a–m were synthesized in short periods of time under microwave conditions in good to excellent yield (54–86%). The chemical structures of these heterocycles consist of a central pyrimidine ring having a phenyl group and pyrimidine groups with sulfonamide motifs. The enzyme inhibitory potential of these compounds was investigated against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) because these enzymes play a crucial role in the treatment of Alzheimer's disease. As compared to the reference compound eserine (IC50  = 0.04 ± 0.0001 μM for AChE and IC50  = 0.85 ± 0.0001 μM for BChE), the IC50 values of the synthesized compounds ranged from 3.73 ± 0.61 μM to 57.36 ± 0.22 μM for AChE and 4.81 ± 0.16 μM to 111.61 ± 0.53 μM for BChE. Among these tested compounds, 6j having a −CH3 group was found to be the most potent one against both enzymes (AChE, IC50  = 3.73 ± 0.61 μM; BChE, IC50  = 4.81 ± 0.16 μM). Quantitative structure–activity relationship (QSAR) and molecular docking studies of the synthesized compounds were also performed. Abstract : A series of 13 novel pyrimidine‐based sulfonamides were synthesized under microwave conditions in good to excellent yield (54–86%). The acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory potential of these compounds was investigated. Compound6j having a –CH3 group was found to be the most potent one against both enzymes (AChE, IC50  = 3.73 ± 0.61 µM; BChE, IC50  = 4.81 ± 0.16 µM).